A Histopathological Study of Hysterectomy Specimens in Gujrat – Pakistan (Medical Forum Monthly, 2024)
Objective: To study the pattern of histopathological lesions in hysterectomy specimens. Study Design: Observational study.Place and Duration of Study: This study was conducted at the Department of Pathology, Nawaz Sharif Medical College, University of Gujrat, Pakistan from Jan 2015 to August 2017.Materials and Methods: The study consisted of 150 uterus specimens that were studied grossly and histologically. These specimens were received at department of Pathology and in a private hospital in Gujrat. The data of all the cases was retrieved from registers of histopathology. It was compiled and analyzed with the help of Microsoft Excel software.Results: Mean age of the patients was 44.7 years in this study. Most (44%) patients were in fifth decade of their life. Chronic cervicitis was the most common finding in the cervix with a frequency of 88.7%. The other lesions were far less common in cervix. Carcinoma cervix was seen in 2.7% of the specimens. Atrophic endometrium, Endometrial Hyperplasia, Endometrial polyp were the three most frequent lesions in endometrium with frequencies of 8.0%, 7.3%, 6.7% respectively. Carcinoma of endometrium was found in 1.3% of cases. Leimomyomas were the most common (44.7%) lesions in myometrium followed by adenomyosis (29.3%). No case of malignancy was found in the myometrium.Conclusion: The findings in our study corroborated well with most studies within as well as outside the country. Among the significant lesions, leiomyomas and adenomyosis were the most common ones.